Three Novel Triterpene Glycosides from the Sea Cucumber Stichopus chloronotus with Potent Cytotoxic Activities (Journal of Basic and Applied Research in Biomedicine, 2024)
This study aimed to isolate the active cytotoxic compounds from Stichopus chloronotus. The isolation process was carried out by using successive separation methods including liquid-liquid partitioning, vacuum liquid chromatography (VLC), size exclusion chromatography, normal and reverse phase chromatography, and HPLC which had been guided by the cytotoxic assay (MTT). The bioassay guided separation technique led to isolation of three new cytotoxic saponins (A, B, and C), which exhibited positive reactions with Liebermann–Burchard reagent. The structures of the isolated compounds were elucidated based on the interpretation of their spectra upon analyzing them with various spectroscopic methods including infra-red spectrophotometry (IR), one and two dimensional nuclear magnetic resonance (NMR), in addition to the positive mode of electrospray mass analysis (+ESI-MS). Based on the analysis, the structures of the isolated compounds were concluded as triterpene glycosides composed of holostane type aglycones attached to various sulphated sugar units.  The molecular formula of the glycoside A was suggested as C66 H104Na2O36S2 (calculated molecular weight = 1583.62 Da), B as C66H103Na3O40S3 (MW= 1701.66 Da) and glycoside C as C66H100Na4O43S4 (MW= 1801.69 Da).  Furthermore, the cytotoxic effects of the isolated glycosides (A, B, and C) were evaluated against various cancer cell lines and found that the glycoside C (IC 50 = 0.9-2.4 µM) was the most potent cytotoxic glycoside, followed by glycoside B (IC 50 = 1.3-2.9 µM) and A (IC50 = 2.4-7.5 µM). These findings, therefore, present S. chloronotus as a promising source of novel cytotoxic saponins with potent anti-cancer activities that require further research into their modes of action and therapeutic applications.